Complications of porcelain fused to metal crowns after five years of cementation at a tertiary care center in Kaski - Tuladhar, Sapna Laxmi; Manandhar, Pratik; Thapa, Neeta; Pradhan, Dilesh; Parajuli, Umesh (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Porcelain fused to metal (PFM) crowns are given to restore badly broken down teeth, to reinforce root canal treated teeth. The common complications are chipped-off porcelain, open contact, dental caries of an abutment, dental caries of adjacent teeth, fracture of an abutment, dislodged crowns, and periodontal problems.Methods: This was a hospital-based cross-sectional study conducted at the outpatient department of Prosthodontics, College of Dental Surgery, Gandaki Medical College. The patients of age group 25 to 50 years who had undergone PFM crowns minimum of five years back in the Department of Prosthodontics were examined for complications of chipped-off porcelain, open contact, periodontal pocket, dislodged crowns, fracture of abutment tooth, caries in abutment and caries in adjacent teeth.Results: The average age was 40.85 ± 8.74 years. The average duration post-cementation of porcelain fused to metal crowns was 6.15±1.52 years. The complications were open contacts 23(28.8%), chipped off porcelain crowns 10(12.5%), periodontitis 4(5.0%), dislodged crown 7(8.8%), fractured abutment 2(2.5%), dental caries in abutment teeth 2(2.5%) and dental caries in adjacent teeth 3(3.8%). Conclusions: The most common complication in porcelain fused to metal crowns post five years of cementation was open contact followed by chipped-off crowns and periodontitis.